2021
DOI: 10.3390/ani11030652
|View full text |Cite
|
Sign up to set email alerts
|

Copper Oxide Nanoparticles Alter Serum Biochemical Indices, Induce Histopathological Alterations, and Modulate Transcription of Cytokines, HSP70, and Oxidative Stress Genes in Oreochromis niloticus

Abstract: In the present study, fish were exposed to sub-lethal doses of CuONPs (68.92 ± 3.49 nm) (10 mg/L, 20 mg/L, and 50 mg/L) for a long exposure period (25 days). Compared to the control group (0.0 mg/L CuONPs), a significant dose-dependent elevation in blood urea and creatinine values, serum alanine transaminase, aspartate transaminase, and alkaline phosphatase enzyme activities were evident in CuONPs-exposed groups (p < 0.05). Fish exposure to 50 mg/L CuONPs significantly upregulated the transcription of pro-i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 76 publications
1
9
0
Order By: Relevance
“…In our study, there was no significant difference in INF-γ concentration among the groups, and HSP-70 was decreased in the HT and HL groups compared with the control group. In a similar sense, the mRNA expression levels of HSP-70 were increased of the Nile tilapia when exposed to toxicants and stressors ( Abdel-Latif et al, 2021a , b ). Additionally, previous research revealed that probiotics Clostridium butyricum could similarly increase the expression of the IL-10 and HSP-70 in weaning rex rabbits ( Liu et al, 2019 ) and colon cancer HT-29 cells ( Andriamihaja et al, 2009 ; Meng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 85%
“…In our study, there was no significant difference in INF-γ concentration among the groups, and HSP-70 was decreased in the HT and HL groups compared with the control group. In a similar sense, the mRNA expression levels of HSP-70 were increased of the Nile tilapia when exposed to toxicants and stressors ( Abdel-Latif et al, 2021a , b ). Additionally, previous research revealed that probiotics Clostridium butyricum could similarly increase the expression of the IL-10 and HSP-70 in weaning rex rabbits ( Liu et al, 2019 ) and colon cancer HT-29 cells ( Andriamihaja et al, 2009 ; Meng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 85%
“…It can accumulate or deplete depending on contaminant. Decrease in WWTP effluent exposure Eelpout—native, spotted snakehead—laboratory, bluegill sunfish ( Lepomis macrochirus )—caged, Mastacembelus armatus —native, Nile tilapia—laboratory Abdel-Latif et al ( 2021 ); Du et al ( 2019 ); Kaur and Dua ( 2014 ); Javed and Usmani ( 2013 ); Fricke et al ( 2012 ) Fibrosis Excess formation and deposition of collagen or fibrous tissue within the parenchyma. Fibrous tissue spreads to fill the gaps left by the retrogressing cells Cod ( Gadus morhua )—native, flatfish—native; eelpout—native, brown trout ( Salmo trutta )—caged, silver catfish—caged, sharptooth catfish—native, flounder, ruffe, and smelt—native ( 2001 ); Peters et al ( 1987 ) Wagenaar and Barnhoorn ( 2018 ); Borucinska et al ( 2017 ); Oliveira et al ( 2015 ); Fricke et al ( 2012 ); Khan ( 2003 ); Schmidt-Posthaus et al Non-specific lesions Lipidosis/steatosis Vacuoles of lipid deposition in the hepatocytes, displacing and compressing the nucleus Flatfish—native, eelpout—native, carp -laboratory, spotted snakehead—laboratory, Nile tilapia ( Oreochromis niloticus ) and mullet ( Mugil cephalus ) —farmed and native; silver catfish—caged, carp—native, sharptooth catfish—native Wagenaar and Barnhoorn ( 2018 ); Oliveira et al ( 2015 ); Kaur and Dua ( 2014 ); Omar et al ( 2013 ); Fricke et al ( 2012 ); Mustafa et al ( 2012 ); Abdel-Moneim and Abdel-Mohsen ( 2010 ); Khan ( 2003 ) Granuloma Inflammatory lesions with dense macrophages in the center and deep basophilic nuclei in the periphery Striped catfish ( Pangasianodon hypophthalmus )—native,eelpout—native, sharptooth catfish—native, dab—native Puttipong et al ( 2020 ); Wagenaar and Barnhoorn ( ...…”
Section: Physiological and Histological Changes Of Livers From Expose...mentioning
confidence: 99%
“…Cells lacking almost all inner organization Cod—native, Flatfish—native, eelpout—native, Mastacembelus armatus —native; Brown trout—caged, carp—laboratory; spotted snakehead—laboratory, Nile tilapia and mullet—farmed and native, silver catfish—caged, carp and sharptooth catfish—native, dab—native, flounder, ruffe, and smelt—native, Prussian carp—native Wagenaar and Barnhoorn ( 2018 ); Borucinska et al ( 2017 ); Lang et al ( 2017 ); Topić Popović et al ( 2016 ); Oliveira et al ( 2015 ); Kaur and Dua ( 2014 ); Javed and Usmani ( 2013 ); Omar et al ( 2013 ); Fricke et al ( 2012 ); Mustafa et al ( 2012 ); Khan ( 2003 ); Schmidt-Posthaus et al ( 2001 ); Johnsen et al ( 1998 ); Peters et al ( 1987 ) Apoptosis Condensed chromatin of hepatocyte nuclei. Cytoplasm fragmented into membrane-bound particles, phagocytic cells Nile tilapia—laboratory, eelpout—native, Prussian carp ( Carassius gibelio ) —native, carp—laboratory Abdel-Latif et al ( 2021 ); Gu et al ( 2021 ); Topić Popović et al ( 2016 ); Fricke et al ( 2012 ) Early toxicopathic lesions Peliosis Presence of intact erythrocytes and eosinophilic serous material within cystic structures Cod—native, Nile tilapia and mullet—farmed and native, flatfish ( Euryglossa orientalis )—native, spotted snakehead—laboratory Borucinska et al ( 2017 ); Chupani et al ( 2013 ); Omar et al ( 2013 ); Roy and Bhattacharya ( 2006 ) Phospholipidosis Enlarged hepatocytes with foamy cytoplasm and numerous intracytoplasmic eosinophilic granules Brown trout—caged, sharptooth catfish—native Abdel-Moneim and Abdel-Mohsen ( 2010 ); Johnsen et al ( 1998 ) …”
Section: Physiological and Histological Changes Of Livers From Expose...mentioning
confidence: 99%
“…On the other hand, in Oreochromis niloticus, 50 mg L −1 caused elevation of the transcripts for SOD, CAT, and GP, but TNFα also showed up-regulation. Additional up-regulated genes consisted of IL-1β, IL-12, Hsp70, and caspase3 [45].…”
Section: Effects Of Copper Nanoparticles On Gene Expressionmentioning
confidence: 99%